A Basic Theory of Everything A Fundamental Theoretical Framework for Science and Philosophy - Søvik, Atle Ottesen (De Gruyter, 2022)
The book presents a theory of what the basic building blocks of the world are and argues that they can be reduced to three: a field, a set of values, and an actualizer. The theory is used to answer philosophical questions like: What are truth, existence, laws of nature, mind, free will, time, mathematical entities, and ethical values? The book is for people who like to ponder the big existential questions, including why there is anything at all.